Analyzing User Satisfaction with Government Websites Through the EUCS and TAM Models - Handayani, Layli; Imtihan, Khairul; Asyari, Hasyim (Jambura Journal of Electrical and Electronics Engineering, 2025)
In the digital era, the quality of public service websites has become a crucial factor in enhancing user engagement and satisfaction. This study aims to evaluate the factors influencing user satisfaction and behavioral intention to use a government service website by integrating the End-User Computing Satisfaction (EUCS) model and the Technology Acceptance Model (TAM). A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance-Performance Map Analysis (IPMA), based on data collected from 346 valid respondents. The results reveal that perceived usefulness and perceived ease of use significantly influence user satisfaction, which subsequently impacts behavioral intention. Additionally, format and timeliness affect perceived usefulness, while format significantly influences perceived ease of use. IPMA analysis identifies perceived ease of use and perceived usefulness as strategic priorities for enhancing user satisfaction and promoting continuous usage. In conclusion, to optimize the effectiveness of digital public services, website administrators should focus on developing intuitive interfaces and delivering services that provide real added value to users.Dalam era digital, kualitas situs web layanan publik menjadi faktor krusial dalam meningkatkan keterlibatan dan kepuasan pengguna. Penelitian ini bertujuan untuk mengevaluasi faktor-faktor yang memengaruhi kepuasan pengguna dan niat perilaku menggunakan situs web layanan pemerintah, dengan mengintegrasikan model End-User Computing Satisfaction (EUCS) dan Technology Acceptance Model (TAM). Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan teknik analisis Partial Least Squares Structural Equation Modeling (PLS-SEM) dan Importance-Performance Map Analysis (IPMA), berdasarkan data dari 346 responden yang valid. Hasil penelitian menunjukkan bahwa perceived usefulness dan perceived ease of use berpengaruh signifikan terhadap user satisfaction, yang selanjutnya berpengaruh terhadap behavioral intention. Selain itu, format dan timeliness memengaruhi perceived usefulness, sedangkan perceived ease of use dipengaruhi oleh format. Analisis IPMA mengidentifikasi perceived ease of use dan perceived usefulness sebagai prioritas utama untuk meningkatkan kepuasan pengguna dan mendorong penggunaan berkelanjutan. Kesimpulannya, untuk meningkatkan efektivitas layanan publik digital, pengelola situs web harus fokus pada pengembangan antarmuka yang intuitif dan layanan yang benar-benar memberikan nilai tambah bagi pengguna.